Self-assembly layer material and preparation method thereof, perovskite solar cell doping and passivating agent, self-assembly layer and solar cell
By introducing compounds with a spiral ring structure into the self-assembly layer material, the problems of poor agglomeration and solubility of self-assembly materials are solved, and a self-assembly layer with high coverage and low defects are achieved, which improves the performance and stability of perovskite solar cells.
Patent Information
- Application Number
- CN202411228212.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-03-28
AI Technical Summary
The existing self-assembled materials form agglomerated molecules through π-π interaction in the solution, resulting in low film coverage, defects, poor infiltration of perovskite solutions and limited solubility.
Compounds with a helical ring structure are introduced into the self-assembly layer material, and the π-π interaction between self-assembly molecules is reduced through the mutually perpendicular spiral ring structure, inhibit molecular agglomeration, and improve solubility and film formation ability.
It achieves good coverage of the substrate by the self-assembly layer material, reduces film defects, improves perovskite crystallinity, reduces interface defects and non-radiative recombination, and improves device stability.
Smart Images

Figure CN119707812A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of solar cells, and in particular to self-assembled layer materials and preparation methods thereof, perovskite solar cell doping and passivation agents, self-assembled layers and solar cells. Background Art
[0002] Perovskite solar cells have attracted widespread attention from industry, academia and research circles due to their advantages such as low preparation cost and adjustable band gap.
[0003] Among them, self-assembled monolayer (SAM) hole transport materials have become a research hotspot due to their low cost, low parasitic absorption, and low material consumption. In particular, samples with controllable surface properties can be prepared through self-assembly, and the perovskite layer can be passivated to reduce interface transmission losses.
[0004] However, existing self-assembled materials will form dimers, trimers and other aggregated molecules through π-π interactions in solution, which leads to low film coverage and many defects. In addition, there are also problems such as poor wettability to perovskite solution and limited solubility. Summary of the invention
[0005] The present application provides a self-assembly layer material and a preparation method thereof, a perovskite solar cell doping and passivation agent, a self-assembly layer and a solar cell, so as to solve the problems of aggregation and poor solubility of self-assembly materials in related technologies.
[0006] In the first aspect, the present application provides a self-assembling layer material having a structural formula as shown in formula (I): (I) Wherein: R includes a group containing carboxyl and / or hydroxyl; R1 and R2 are each independently selected from any one of -H, -I, -Cl, -Br, -CH3, -OCH3; The substitution position of R1 and R2 is any carbon atom on the benzene ring; n is a positive integer ranging from 1 to 10.
[0007] The present application introduces a compound with a structure as shown in formula (I) into the self-assembled layer material so that the mutually perpendicular spirocyclic structure can effectively reduce the π-π interaction between the self-assembled molecules, thereby inhibiting the aggregation of molecules, achieving good coverage of the self-assembled layer material on the substrate, and reducing the film defects of the self-assembled layer. The spirocyclic structure increases the solubility of the self-assembled layer material in the solution, obtains good film-forming ability, further affects the crystallinity of the perovskite, reduces the interface defects of the perovskite, and reduces non-radiative recombination. The introduction of the rigid spirocyclic structure gives the molecule good stability, which can better hinder the interface reaction and improve the stability of the device. The group containing carboxyl and / or hydroxyl can be used as an anchoring group to undergo a firm self-assembly with the substrate surface by covalent bonding.
[0008] n is a positive integer from 1 to 10 to achieve different chain lengths and different molecular stacking.
[0009] R1 and R2 are independently selected from any one of -H, -I, -Cl, -Br, -CH3, and -OCH3, that is, the hydrogen atoms on the corresponding benzene rings may be substituted or not. When the hydrogen atoms on the corresponding benzene rings are substituted, the substituent groups are selected from any one of -H, -I, -Cl, -Br, -CH3, and -OCH3.
[0010] The substitution position of R1 and R2 is any carbon atom on the benzene ring, that is, the substitution position of the substituent on the corresponding benzene ring is not limited, and can be any one of the six carbon atoms on the corresponding benzene ring. It should be noted that the same benzene ring can be substituted with multiple identical substituents.
[0011] In some embodiments, in the self-assembling layer material, R includes any one of a phosphate group, a carboxyl group and a sulfonic acid group. The phosphate group has two -OH groups and one -P=O, and can be combined with a substrate material such as conductive glass to anchor the self-assembling layer material on the base material, and undergo a strong self-assembly with the substrate surface by covalent bonding; the carboxyl group contains -COOH, and can also be combined with a substrate material such as conductive glass to anchor the self-assembling layer material on the base material, and undergo a strong self-assembly with the substrate surface by covalent bonding; the sulfonic acid group contains -S=O and -OH, and can be combined with a substrate material such as conductive glass to anchor the self-assembling layer material on the base material, and undergo a strong self-assembly with the substrate surface by covalent bonding; and / or, n is a positive integer from 2 to 4, which can make the anchoring group in good contact with the substrate.
[0012] In some embodiments, the self-assembling layer material includes (2-(10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, (2-(10H-spiro[acridine-9,9'-fluorene]-10-yl)propyl)phosphoric acid, (2-(10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dibromo-10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, (2-(3',6'-dibromo-10H-spiro[acridine-9,9'-fluorene]-10-yl)propyl)phosphoric acid, (2-(3',6'-dibromo-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dimethyl-10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, At least one of (2-(3',6'-dimethyl-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dimethyl-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dimethoxy-10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, (2-(3',6'-dimethoxy-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, and (2-(3',6'-dimethoxy-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid. Selecting at least one of the above hole layer transport layer materials can provide more anchoring groups, thereby improving the anchoring effect and self-assembly effect between the hole layer transport layer material and the substrate material.
[0013] In a second aspect, the present application proposes a method for preparing a self-assembly layer material, comprising the following steps: Compound A is reacted with sodium hydride in a mixed solution of dibromoalkane and NN-dimethylformamide (DMF) to obtain compound B; Reacting compound B with triethyl phosphite to obtain compound C; Reacting compound C with bromotrimethylsilane in a solvent to obtain a self-assembly layer material; Wherein, compound A has a structural formula as shown in formula (II), compound B has a structural formula as shown in formula (III), compound C has a structural formula as shown in formula (IV), and the self-assembly layer material has a structural formula as shown in formula (V);
[0014] (II) (III) (IV) (V) Wherein: R1 and R2 are independently selected from any one of -H, -I, -Cl, -Br, -CH3, -OCH3; The substitution position of R1 and R2 is any carbon atom on the benzene ring; n is a positive integer ranging from 1 to 10.
[0015] Compound B is generated by the substitution reaction of dibromoalkane, compound C is generated by the nucleophilic substitution reaction of compound B, and self-assembled layer material is generated by the hydrolysis reaction of compound C. By introducing a compound with a structure as shown in formula (V) into the self-assembled layer material, the mutually perpendicular spirocyclic structure can effectively reduce the π-π interaction between the self-assembled molecules, thereby inhibiting the agglomeration of molecules, achieving good coverage of the self-assembled layer material on the substrate, and reducing the film defects of the self-assembled layer. The spirocyclic structure increases the solubility of the self-assembled layer material in the solution, obtains good film-forming ability, further affects the crystallinity of the perovskite, reduces the interface defects of the perovskite, and reduces non-radiative recombination. The introduction of the rigid spirocyclic structure gives the molecule good stability, which can better hinder the interface reaction and improve the stability of the device. The hydroxyl-containing group can be used as an anchoring group to form a strong self-assembly with the substrate surface by covalent bonding. It can also be used as a passivating agent doping to passivate the upper and lower interfaces of the perovskite by molecular extrusion to reduce the non-radiative recombination of carriers at the interface.
[0016] In some embodiments, the dibromoalkane includes at least one of 1,2-dibromoethane, 1,3-dibromopropane and 1,4-dibromobutane. Using at least one of the above dibromoalkane can effectively carry out nucleophilic substitution.
[0017] In some embodiments, the molar ratio of compound A, sodium hydride and dibromoalkane is 1:(3-5):(12-18). The molar ratio of compound A, sodium hydride and dibromoalkane within this range can increase the yield of compound B. Preferably, the molar ratio of compound A, sodium hydride and dibromoalkane is 1:4:15.
[0018] In some embodiments, the molar ratio of compound B to triethyl phosphite is 1:(10-25). When the molar ratio of compound B to triethyl phosphite is within this range, sufficient phosphorus-oxygen bonds can be effectively introduced. Preferably, the molar ratio of compound B to triethyl phosphite is 1:20.
[0019] In some embodiments, the molar ratio of compound C to bromotrimethylsilane is 1:(5-15). The molar ratio of compound C to bromotrimethylsilane within this range can improve the hydrolysis efficiency of compound C. Preferably, the molar ratio of compound C to bromotrimethylsilane is 1:10.
[0020] In a third aspect, the present application proposes a perovskite solar cell dopant, comprising the self-assembled layer material of the first aspect.
[0021] In a fourth aspect, the present application proposes a perovskite solar cell passivator, comprising the self-assembled layer material of the first aspect.
[0022] In a fifth aspect, the present application proposes a self-assembly layer, comprising the self-assembly layer material of the first aspect.
[0023] In a sixth aspect, the present application proposes a solar cell comprising the self-assembled layer of the fifth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 This is the hydrogen spectrum of compound B prepared from the self-assembled layer material of Example 6 of the present application.
[0026] Figure 2 This is the hydrogen spectrum of compound C prepared from the self-assembled layer material of Example 6 of the present application.
[0027] Figure 3 This is a hydrogen spectrum of the self-assembled layer material prepared by the self-assembled layer material of Example 6 of the present application.
[0028] Figure 4 This is a JV curve diagram of a solar cell prepared with the self-assembled layer material of Example 6 of the present application.
[0029] Figure 5 This is an infrared spectrum of the self-assembled layer prepared by the self-assembled layer material of Example 6 of the present application. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
[0031] Perovskite solar cells have attracted extensive attention from industry, academia and research circles due to their advantages such as low preparation cost and adjustable band gap. Among them, self-assembled layer materials (SAM) hole transport materials are widely used in the preparation of perovskite solar cells due to their low cost, low parasitic absorption and low material consumption. In particular, samples with controllable surface properties can be prepared by self-assembly, and the perovskite layer can be passivated to reduce interface transmission losses. It is suitable for spin coating, scraping, slit coating, spraying, vacuum evaporation, immersion, fumigation and other methods.
[0032] However, existing self-assembled materials will form dimers, trimers and other aggregated molecules through π-π interactions in solution, which leads to low film coverage and many defects. In addition, there are also problems such as poor wettability to perovskite solution and limited solubility.
[0033] In view of this, the present application provides a self-assembly layer material and a preparation method thereof, a perovskite solar cell doping and passivation agent, a self-assembly layer and a solar cell to solve the problems of aggregation and poor solubility of self-assembly materials in related technologies.
[0034] In the first aspect, the present application provides a self-assembling layer material having a structural formula as shown in formula (I): (I) Wherein: R includes a group containing carboxyl and / or hydroxyl; R1 and R2 are each independently selected from any one of -H, -I, -Cl, -Br, -CH3, -OCH3; The substitution position of R1 and R2 is any carbon atom on the benzene ring; n is a positive integer ranging from 1 to 10.
[0035] The present application introduces a compound with a structure as shown in formula (I) into the self-assembled layer material so that the mutually perpendicular spirocyclic structure can effectively reduce the π-π interaction between the self-assembled molecules, thereby inhibiting the aggregation of molecules, achieving good coverage of the substrate by the self-assembled layer material, and reducing the film defects of the self-assembled layer. The spirocyclic structure increases the solubility of the self-assembled layer material in the solution, obtains good film-forming ability, further affects the crystallinity of the perovskite, reduces the interface defects of the perovskite, and reduces non-radiative recombination. The introduction of the rigid spirocyclic structure gives the molecule good stability, which can better hinder the interface reaction and improve the stability of the device. The carboxyl and / or hydroxyl-containing groups can be used as anchoring groups to undergo firm self-assembly with the substrate surface by covalent bonding and passivate the perovskite interface defects.
[0036] n is a positive integer from 1 to 10, which can make the anchoring group in good contact with the substrate.
[0037] R1 and R2 are independently selected from any one of -H, -I, -Cl, -Br, -CH3, and -OCH3, that is, the hydrogen atoms on the corresponding benzene rings may be substituted or not. When the hydrogen atoms on the corresponding benzene rings are substituted, the substituent groups are selected from any one of -H, -I, -Cl, -Br, -CH3, and -OCH3.
[0038] The substitution position of R1 and R2 is any carbon atom on the benzene ring, that is, the substitution position of the substituent on the corresponding benzene ring is not limited, and can be any one of the six carbon atoms on the corresponding benzene ring. It should be noted that the same benzene ring can be substituted with multiple identical substituents.
[0039] In combination with the first aspect, in some embodiments of the present application, in the self-assembling layer material, R includes any one of a phosphate group, a carboxyl group and a sulfonic acid group. The phosphate group has two -OH groups and one -P=O, and can be combined with a substrate material such as conductive glass to anchor the self-assembling layer material on the base material, and undergo a firm self-assembly with the substrate surface through covalent bonding; the carboxyl group contains -COOH, and can also be combined with a substrate material such as conductive glass to anchor the self-assembling layer material on the base material, and undergo a firm self-assembly with the substrate surface through covalent bonding; the sulfonic acid group contains -S=O and -OH, and can be combined with a substrate material such as conductive glass to anchor the self-assembling layer material on the base material, and undergo a firm self-assembly with the substrate surface through covalent bonding.
[0040] In combination with the first aspect, in some embodiments of the present application, n is a positive integer from 2 to 4, which can enable the anchoring group to be in good contact with the substrate.
[0041] In combination with the first aspect, in some embodiments of the present application, the self-assembly layer material includes (2-(10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, (2-(10H-spiro[acridine-9,9'-fluorene]-10-yl)propyl)phosphoric acid, (2-(10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dibromo-10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, (2-(3',6'-dibromo-10H-spiro[acridine-9,9'-fluorene]-10-yl)propyl)phosphoric acid, (2-(3',6'-dibromo-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dimethyl-10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, At least one of (2-(3',6'-dimethyl-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dimethyl-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dimethoxy-10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, (2-(3',6'-dimethoxy-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, and (2-(3',6'-dimethoxy-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid. Selecting at least one of the above hole layer transport layer materials can provide more anchoring groups, thereby improving the anchoring effect and self-assembly effect between the hole layer transport layer material and the substrate material.
[0042] In a second aspect, the present application proposes a method for preparing a self-assembly layer material, comprising the following steps: Compound A is reacted with sodium cyanide in a mixed solution of dibromoalkane and NN-dimethylformamide (DMF) to obtain compound B; Reacting compound B with triethyl phosphite to obtain compound C; Reacting compound C with bromotrimethylsilane in a solvent to obtain a self-assembly layer material; Wherein, compound A has a structural formula as shown in formula (II), compound B has a structural formula as shown in formula (III), compound C has a structural formula as shown in formula (IV), and the self-assembly layer material has a structural formula as shown in formula (V);
[0043] (II) (III) (IV) (V) Wherein: R1 and R2 are independently selected from any one of -H, -I, -Cl, -Br, -CH3, -OCH3; The substitution position of R1 and R2 is any carbon atom on the benzene ring; n is a positive integer from 1 to 10. n can be 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0044] Compound B is generated through the coupling reaction of dibromoalkane, compound C is generated through the nucleophilic substitution reaction of compound B, and self-assembled layer material is generated through the hydrolysis reaction of compound C. By introducing a compound with a structure as shown in formula (V) into the self-assembled layer material, the mutually perpendicular spirocyclic structure can effectively reduce the π-π interaction between the self-assembled molecules, thereby inhibiting the agglomeration of molecules, achieving good coverage of the self-assembled layer material on the substrate, and reducing the film defects of the self-assembled layer. The spirocyclic structure increases the solubility of the self-assembled layer material in the solution, obtains good film-forming ability, further affects the crystallinity of the perovskite, reduces the interface defects of the perovskite, and reduces non-radiative recombination. The introduction of the rigid spirocyclic structure gives the molecule good stability, which can better hinder the interface reaction and improve the stability of the device. The phosphoric acid-containing group can be used as an anchoring group to form a strong self-assembly with the substrate surface through covalent bonding.
[0045] In conjunction with the second aspect, in some embodiments of the present application, the dibromoalkane includes at least one of 1,2-dibromoethane, 1,3-dibromopropane and 1,4-dibromobutane. By using at least one of the above dibromoalkane, an alkyl chain can be introduced through nucleophilic substitution.
[0046] In combination with the second aspect, in some embodiments of the present application, the molar ratio of compound A, sodium hydride and dibromoalkane is 1: (3-5): (12-18). When the molar ratio of compound A, sodium hydride and dibromoalkane is within this range, the yield of compound B can be increased. The molar ratio of compound A, sodium hydride and dibromoalkane includes but is not limited to 1:3:12, 1:3:18, 1:5:12, 1:5:18. Preferably, the molar ratio of compound A, sodium hydride and dibromoalkane is 1:4:15.
[0047] In conjunction with the second aspect, in some embodiments of the present application, the molar ratio of compound B to triethyl phosphite is 1:(10-25). Within this range, the molar ratio of compound B to triethyl phosphite can introduce sufficient phosphorus-oxygen bonds, and the molar ratio of compound B to triethyl phosphite includes but is not limited to 1:10, 1:12, 1:15, 1:18:1:20, 1:22 or 1:25. Preferably, the molar ratio of compound B to triethyl phosphite is 1:20.
[0048] In combination with the second aspect, in some embodiments of the present application, the molar ratio of compound C to bromotrimethylsilane is 1: (5-15). The molar ratio of compound C to bromotrimethylsilane within this range can improve the hydrolysis efficiency of compound C. The molar ratio of compound C to bromotrimethylsilane includes but is not limited to 1: 5, 1: 6, 1: 7, 1: 8, 1: 9, 1: 10, 1: 11, 1: 12, 1: 13, 1: 14 or 1: 15. Preferably, the molar ratio of compound C to bromotrimethylsilane is 1: 10.
[0049] In a third aspect, the present application proposes a perovskite solar cell dopant, comprising the self-assembled layer material of the first aspect.
[0050] In a fourth aspect, the present application proposes a perovskite solar cell passivator, comprising the self-assembled layer material of the first aspect.
[0051] In a fifth aspect, the present application proposes a self-assembly layer, comprising the self-assembly layer material of the first aspect.
[0052] In a sixth aspect, the present application proposes a solar cell comprising the self-assembled layer of the fifth aspect.
[0053] In combination with the sixth aspect, in some embodiments of the present application, the solar cell includes a conductive glass layer, a self-assembled layer, a perovskite active layer, an electron transport layer, a barrier layer and a metal electrode layer arranged in sequence. As an example, the following method can be used to prepare the conductive glass: FTO (fluorine-doped tin oxide) or conductive glass (indium tin oxide) is ultrasonically cleaned for 30 minutes with detergent, deionized water, acetone and isopropanol in sequence, and after drying with nitrogen, the conductive glass is plasma cleaned for 15 minutes to obtain the conductive glass; the self-assembled layer material is dissolved in ethanol to prepare 0.25-1 mg mL -1 The solution was stirred at 3000 rmp s -1 The self-assembled layer was obtained by spin coating on the conductive glass at a speed of 1000 rpm for 30 s, followed by annealing at 100 °C for 10 min. The perovskite precursor solution with a concentration of 1.5 M was prepared on the self-assembled layer by spin coating. The spin coating was divided into two stages. The speed of the first stage was 1000 rpm s -1 , spin coating for 10 s, second stage at 4000 rpm s -1 The perovskite active layer was obtained by vacuum evaporation at 0.2 Å s -1 20 nm of C is deposited at a rate of 60 , and then at 0.2 Å s -18 nm BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) was deposited at a rate of 1000 nm to obtain an electron transport layer; a metal electrode or a carbon electrode was deposited as a back electrode using a vacuum evaporator. The barrier layer was purchased from Alfa Aesar (BCP, 99.5%).
[0054] In combination with the sixth aspect, in some embodiments of the present application, the solar cell includes a conductive glass layer, a self-assembled layer (2 layers in total, a nickel oxide vacancy layer in contact with the conductive glass layer, and a modified layer containing self-assembled layer materials), a perovskite active layer, an electron transport layer, a blocking layer and a metal electrode layer arranged in sequence.
[0055] In combination with the sixth aspect, the present application proposes that the self-assembled layer doped with perovskite realizes molecular extrusion, which can be realized by the following method: doping 1 mg L -1 The perovskite precursor solution of the self-assembled layer was prepared on the substrate by spin coating. The spin coating was divided into two stages. The speed of the first stage was 1000 rpm s -1 , spin coating for 10 s, second stage at 4000 rpm s -1 The perovskite active layer was obtained by vacuum evaporation at 0.2 Å s -1 20 nm of C is deposited at a rate of 60 , then at 0.2 Ås -1 8 nm BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) was deposited at a speed of 1000 rpm to obtain an electron transport layer; the back electrode was deposited by vacuum evaporation. The blocking layer was purchased from Alfa Aesar (BCP, 99.5%).
[0056] The technical solution provided in this application is described in detail below with reference to the embodiments and drawings.
[0057] Example 1 Embodiment 1 of the present application provides a self-assembly layer material having a structural formula as shown in formula (VI).
[0058]
[0059] (VI) Example 2 Example 2 of the present application provides a self-assembly layer material having a structural formula as shown in formula (VII).
[0060]
[0061] (VII) Example 3 Example 3 of the present application provides a self-assembly layer material having a structural formula as shown in formula (VIII).
[0062]
[0063] (VIII) Example 4 Example 4 of the present application provides a self-assembly layer material having a structural formula as shown in formula (IX).
[0064]
[0065] (IX) Example 5 Example 5 of the present application provides a self-assembly layer material having a structural formula as shown in formula (X).
[0066]
[0067] (Ⅹ) Example 6 Embodiment 6 of the present application provides a method for preparing a self-assembly layer material, comprising the following steps: Compound A containing a spirocyclic structure is coupled with sodium hydride (NaH) in a mixed solution of 1,4-dibromobutane and NN-dimethylformamide (DMF) to obtain compound B, wherein the molar ratio of compound A, sodium hydride, and dibromoalkyl is 1:4:15, the coupling reaction temperature is 70°C, and the coupling reaction time is 24h; after the reaction, the reaction is quenched with water, and the solution is extracted with water and dichloromethane three times, the organic layer is dried with anhydrous sodium sulfate, and the solvent is removed by rotary evaporation to obtain a crude product, and the crude product is separated by silica gel flow column chromatography with a mixed solution of petroleum ether and dichloromethane to obtain compound B with a yield of 79%. Its hydrogen spectrum is as follows Figure 1 As shown, 1 H NMR (400 MHz, DMSO-d6) δ 7.93–7.85 (m, 2H), 7.35 (td, J =7.3, 1.4 Hz, 2H), 7.24–7.10 (m, 8H), 6.56 (ddd, J = 8.0, 6.8, 1.4 Hz, 2H), 6.19 (dd, J = 7.7, 1.5 Hz, 2H), 4.10 (d, J = 8.3 Hz, 2H), 2.09 (p, J = 6.8Hz, 2H), 1.95 (d, J = 8.3 Hz, 2H); Compound B and triethyl phosphite mixed solution undergo nucleophilic substitution reaction to generate compound C. The molar ratio of compound B to triethyl phosphite is 1:20. The substitution reaction is carried out under reflux conditions for 24 hours. After the reaction, the mixture is cooled to room temperature, petroleum ether is added and stirred under ice bath conditions, the solid is filtered out and washed with petroleum ether to obtain compound C with a yield of 78%. Its hydrogen spectrum is shown as follows Figure 2 As shown, 1 H NMR (400 MHz, DMSO-d6) δ 7.89 (d, J =7.6 Hz, 2H), 7.34 (td, J = 7.4, 1.3 Hz, 2H), 7.24–7.09 (m, 8H), 6.60–6.51 (m,2H), 6.18 (dd, J = 7.7, 1.5 Hz, 2H), 4.14–3.88 (m, 6H), 1.89 (dd, J = 16.9,8.5 Hz, 4H), 1.28–1.14 (m, 10H); Compound C was hydrolyzed in a mixed solution of bromotrimethylsilane and 1,4-dioxane to prepare a self-assembled layer material. The molar ratio of compound C to bromotrimethylsilane was 1:10, the solvent was 1,4-dioxane, the hydrolysis temperature was room temperature, the hydrolysis time was 24h, and after the reaction, distilled water was added dropwise and stirred for 3h. The solid was then filtered out and recrystallized with ethanol to obtain a self-assembled layer material with a yield of 58%). Its hydrogen spectrum is shown as follows Figure 3 As shown, 1 H NMR (400 MHz, DMSO-d6) δ 7.92 (dt, J = 7.7, 1.0 Hz, 2H), 7.38 (td, J = 7.3, 1.4 Hz, 2H), 7.26–7.14 (m, 8H), 6.59 (ddd, J = 8.0, 6.4, 1.7 Hz, 2H), 6.22 (dd, J = 7.8, 1.4Hz, 2H), 4.08 (t, J = 8.0 Hz, 2H), 1.95 (s, 2H), 1.80–1.64 (m, 4H).
[0068] The reaction equation is: .
[0069] The self-assembled layer material prepared in Example 6 was used as a self-assembled layer to prepare a perovskite solar cell and test its photovoltaic performance. Its structure was: glass / conductive glass / SAM / perovskite / C60 / BCP / Cu. The conductive glass was ultrasonically cleaned with detergent, deionized water, acetone and isopropanol for 30 minutes in sequence. After drying with nitrogen, the conductive glass was plasma cleaned for 15 minutes. The self-assembled layer material dissolved in ethanol (0.5 mg mL -1 ), then 150 μL of the solution was dropped on a conductive glass substrate, spin coated at 3000 rpm / min for 30 seconds, and then annealed at 100°C for 10 minutes. Then 100 μL of the precursor was dropped on the SAM layer and quickly spin coated in two steps, i.e., 1000 rpm for 10 seconds and 4,000 rpm for 30 seconds, and 150 μL of toluene was dropped as an antisolvent 10 seconds before the end of the second step. The prepared perovskite film was then annealed at 100°C for 60 minutes, followed by vacuum evaporation at 0.2 Å s -1 20 nm of C is deposited at a rate of 60 , with a value of 0.2 Å s -1 8 nm BCP was deposited at a rate of 100 nm and 100 nm Cu was used as the electrode. The WACOM Class AAA (WXS-100S-5) simulator was used in air at 100 mW / cm 2 The current-voltage ( J - V ) curve (2400Series Source Meter, Keithley Instruments), the active area of the solar cell measured under AM 1.5 G conditions is 0.07 square centimeters, determined by the opaque mask. J - V The curve results are as follows Figure 4 As shown. Figure 4 It can be seen that the self-assembled layer prepared using the spirocyclic structure has good photoelectric properties and achieves a higher filling factor and open circuit voltage, which is due to the good covering ability of the self-assembled molecules.
[0070] The self-assembled monolayer of the self-assembled layer material prepared in Example 6 and the self-assembled layer assembled on the conductive glass were subjected to infrared spectroscopy tests. Figure 5 As shown in the figure, there is a clear difference in the infrared spectra of the self-assembled layer material before and after assembly on the conductive glass. In the infrared spectrum of the self-assembled layer material before assembly, the peak at 1256 cm-1 is attributed to the stretching vibration of the −P=O bond, and the peak at 991 cm-1 is attributed to the stretching vibration of the −P=O bond. -1 and 930cm -1The peaks nearby are related to the asymmetric stretching vibration and symmetric stretching vibration of −P−OH, respectively; after the self-assembled layer material is combined with the conductive glass surface, the stretching vibration of the −P=O bond moves to a lower wavenumber, and the vibration peak of −P−OH moves to a higher wavenumber. The above data indicate that the self-assembled layer material is adsorbed on the conductive glass surface through a more stable tridentate bond, thereby achieving good coverage.
[0071] Example 7 Embodiment 7 of the present application provides a method for preparing a self-assembly layer material, comprising the following steps: Compound A containing a spirocyclic structure as shown in formula (II) is subjected to coupling reaction with sodium hydride (NaH) in a mixed solution of 11-bromodecanoic acid methyl ester and NN-dimethylformamide (DMF) to obtain compound B, wherein the molar ratio of compound A, sodium hydride and dibromoalkyl is 1:4:15, the coupling reaction temperature is 70°C, and the coupling reaction time is 24h. After the reaction, water is added, the solid is filtered out and then washed with water for multiple times. After the solid is dissolved in DMSO, lithium hydroxide is added and stirred for 3 hours. After the stirring is completed, 2 mol / L hydrochloric acid is added for acidification, water is added, and the solid is filtered out to obtain a self-assembled layer material shown in formula (VII).
[0072] Example 8 Embodiment 8 of the present application provides a method for preparing a self-assembly layer material, comprising the following steps: Compound A containing a spirocyclic structure as shown in formula (II) is coupled with sodium hydride (NaH) in a mixed solution of sodium 2-bromoethylsulfonate and NN-dimethylformamide (DMF) to obtain compound B, wherein the molar ratio of compound A, sodium hydride and dibromoalkyl is 1:4:15, the coupling reaction temperature is 70°C, and the coupling reaction time is 24h; after the reaction, 2mol / L hydrochloric acid is added for acidification, water is added, the solid is filtered out, and washed with water several times to obtain a self-assembled layer material represented by formula (VIII).
[0073] Comparative Example 1 Comparative Example 1 of the present application provides a self-assembling layer material [2-(9H-carbazole-9-yl)ethyl]phosphoric acid, the structural formula of which is shown in Formula (XI):
[0074] (Ⅺ) The self-assembled material of the carbazole core of Comparative Example 1 will form dimers, trimers and other aggregated molecules through π-π interactions in the solution, resulting in low film coverage and many defects. In addition, there are problems such as poor wettability to perovskite solution and limited solubility.
[0075] In summary, by introducing a compound with a structure as shown in formula (I) into the self-assembled layer material, the mutually perpendicular spirocyclic structure can effectively reduce the π-π interaction between the self-assembled molecules, thereby inhibiting the aggregation of molecules, achieving good coverage of the self-assembled layer material on the substrate, and reducing the film defects of the self-assembled layer. The spirocyclic structure increases the solubility of the self-assembled layer material in the solution, obtains good film-forming ability, further affects the crystallinity of the perovskite, reduces the interface defects of the perovskite, and reduces non-radiative recombination. The introduction of the rigid spirocyclic structure gives the molecule good stability, which can better hinder the interface reaction and improve the stability of the device. The carboxyl and / or hydroxyl-containing groups can be used as anchoring groups to form a strong self-assembly with the substrate surface by covalent bonding.
[0076] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.
[0077] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.
[0078] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A self-assembly layer material, characterized in that: It has the structural formula shown in formula (I): (Ⅰ) Wherein: R includes a group containing carboxyl and / or hydroxyl groups; R1 and R2 are each independently selected from any one of -H, -I, -Cl, -Br, -CH3, -OCH3; The substitution position of R1 and R2 is any carbon atom on the benzene ring; n is a positive integer ranging from 1 to 10.
2. The self-assembled layer material according to claim 1, characterized in that R includes any one of a phosphate group, a carboxyl group and a sulfonic acid group; and / or, n is a positive integer from 2 to 4.
3. The self-assembled layer material according to claim 1, characterized in that The self-assembly layer material includes (2-(10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, (2-(10H-spiro[acridine-9,9'-fluorene]-10-yl)propyl)phosphoric acid, (2-(10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dibromo-10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, (2-(3',6'-dibromo-10H-spiro[acridine-9,9'-fluorene]-10-yl)propyl)phosphoric acid, (2-(3',6'-dibromo-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dimethyl-10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, At least one of (2-(3',6'-dimethyl-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dimethyl-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, (2-(3',6'-dimethoxy-10H-spiro[acridine-9,9'-fluorene]-10-yl)ethyl)phosphoric acid, (2-(3',6'-dimethoxy-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid, and (2-(3',6'-dimethoxy-10H-spiro[acridine-9,9'-fluorene]-10-yl)butyl)phosphoric acid.
4. A method for preparing a self-assembly layer material, characterized in that: The following steps are involved: Compound A is reacted with sodium hydride in a mixed solution of dibromoalkane and NN-dimethylformamide (DMF) to obtain compound B; Reacting compound B with triethyl phosphite to obtain compound C; Reacting compound C with bromotrimethylsilane in a solvent to obtain a self-assembly layer material; Wherein, compound A has a structural formula as shown in formula (II), compound B has a structural formula as shown in formula (III), compound C has a structural formula as shown in formula (IV), and the self-assembly layer material has a structural formula as shown in formula (V); (Ⅱ)(Ⅲ)(Ⅳ)(Ⅴ) Wherein: R1 and R2 are each independently selected from any one of -H, -I, -I, -Cl, -Br, -CH3, -OCH3; The substitution position of R1 and R2 is any carbon atom on the benzene ring; n is a positive integer ranging from 1 to 10.
5. The method for preparing the self-assembly layer material according to claim 4, characterized in that: The dibromoalkane includes at least one of 1,2-dibromoethane, 1,3-dibromopropane and 1,4-dibromobutane.
6. The method for preparing the self-assembly layer material according to claim 4, characterized in that: The molar ratio of compound A, sodium hydride and dibromoalkane is 1:(3-5):(12-18).
7. The method for preparing the self-assembly layer material according to claim 4, characterized in that: The molar ratio of compound B to triethyl phosphite is 1:(10-25).
8. The method for preparing the self-assembly layer material according to claim 4, characterized in that: The molar ratio of compound C to bromotrimethylsilane is 1:(5-15).
9. A perovskite solar cell dopant, characterized in that: The invention comprises the self-assembled layer material as claimed in any one of claims 1 to 3, or the self-assembled layer material prepared by the preparation method of the self-assembled layer material as claimed in any one of claims 4 to 8.
10. A perovskite solar cell passivator, characterized in that: The invention comprises the self-assembled layer material as claimed in any one of claims 1 to 3, or the self-assembled layer material prepared by the preparation method of the self-assembled layer material as claimed in any one of claims 4 to 8.
11. A self-assembled layer, characterized in that The invention comprises the self-assembled layer material as claimed in any one of claims 1 to 3, or the self-assembled layer material prepared by the preparation method of the self-assembled layer material as claimed in any one of claims 4 to 8.
12. A solar cell, characterized in that: Comprising the self-assembled layer as claimed in claim 11.
Citation Information
Patent Citations
Spiro organic compound and application thereof in organic electronic device
CN117447515A
Interface modification layer material and perovskite solar cell using same
CN117586301A
Perovskite precursor solution, perovskite thin film preparation method and solar cell
CN117998953A
Self-assembled monomolecular layer, perovskite solar cell and preparation method of perovskite solar cell
CN118317668A
Spiro self-assembly monomolecular hole transport material and preparation method and application thereof
CN118373847A